Welfare effects of property taxation - Max Löffler; Sebastian Siegloch (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2021)
We analyze the welfare implications of property taxation. Using a sufficient statistics approach, we show that the tax incidence depends on how housing prices, labor and other types of incomes as well as public services respond to property tax changes. Empirically, we exploit the German institutional setting with 5,200 municipal tax reforms for identification. We find that higher taxes are fully passed on to rental prices after three years. The pass-through is lower when housing supply is inelastic. Combining reduced form estimates with our theoretical framework, we simulate the welfare effects of property taxes and show that they are regressive.
Keywords: H22; H41; H71; R13; R31; R38; 330; property taxation; welfare; tax incidence; local labor markets; rental housing